2000
DOI: 10.3354/meps193305
|View full text |Cite
|
Sign up to set email alerts
|

High survival of neustonic zoea I larvae of American lobster Homarus americanus following short-term exposure to ultraviolet radiation (280 to 400 nm)

Abstract: Ultraviolet radlation (UV-B = 280 to 320 nm, UV-A = 320 to 400 nm) is harmful to the plankton~c early life stages of some marine organisms In the Gulf of St. Lawrence, Canada, measurements of the diffuse attenuation coefficients have indicated that the maxlmum depth to which 10Q,G of the surface energy penetrates at 310 nm is 3 m. Thus, organisms residing in this surface layer are exposed to UV radiation. During the summer spawning season (May to September), the first zoeal larval stages of the American lobste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Lobster larvae may therefore be exposed to high doses of UV radiation; yet larvae exposed to radiation had a mortality rate comparable to that of protected larvae. 138 This outcome suggests that lobster larvae are tolerant to UV radiation. A combination of adaptations to planktonic life near the surface, such as production of light-blocking pigments and other effective mechanisms, may account for the relative resistance of lobster larvae to UV radiation.…”
Section: Secondary Consumersmentioning
confidence: 98%
“…Lobster larvae may therefore be exposed to high doses of UV radiation; yet larvae exposed to radiation had a mortality rate comparable to that of protected larvae. 138 This outcome suggests that lobster larvae are tolerant to UV radiation. A combination of adaptations to planktonic life near the surface, such as production of light-blocking pigments and other effective mechanisms, may account for the relative resistance of lobster larvae to UV radiation.…”
Section: Secondary Consumersmentioning
confidence: 98%
“…Finally, chemical cues, which are necessary for larval settlement, might be destroyed by UVR. It has been demonstrated that most larvae require specific chemical cues for settlement (see reviews : Scheltema 1974, Pawlik 1992, Rodriguez et al 1993. Biofilms, which mainly consist of bacteria and diatoms, are known to induce settlement of H. elegans (Hadfield et al 1994, Qiu & Qian 1997, Unabia & Hadfield 1999, Lau & Qian 2001, Harder et al 2002, Lau et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…cit.). For these reasons, it would be very useful to understand how the neuston is influenced by environmental and oceanographic factors, including temperature, solar radiation, salinity, and acidification (Hardy, 1991;Rodríguez et al 2000;Zaitsev, op. cit.…”
Section: Introductionmentioning
confidence: 99%